f(x)= -2x-3
Step-by-step explanation:
Step 1:
Let the sequence given here is -5, -7, -9, -11, -13 ......
Here the first term (a₁) of sequence is -5
And the common difference between the numbers in the sequence is
d= (-7-(-5)) = -7+5 = -2
Let the number of terms be x
Step 2;
To find the sequence function basic arithmetic sequence formula is
aₙ = a₁ + d( x-1)
Applying the values we get
f(X) = -5 + ((-2)(X-1))
on simplification
f(X) = -5 + (-2X+2)
f(X)= -5+2-2X
f(X)= -3-2X
Answer:
Step-by-step explanation:
Option B
Because if you start with one dollar and by day 3 you get 301 dollars and option A only gives you 8 cents on day 3 you get more money by the end of the month if you choose option B.
Answer:
96
Step-by-step explanation:
8x(5+7)
Parentheses first
8* (12)
Then multiply
96
The ordered pairs would be (x-2, -y).
Translating a graph to the right subtracts the number of units from the x-coordinate.
Reflecting across the x-axis negates the y-coordinate.
Answer: C. 71,224,900
Based on the power, move the decimal point that many spaces to the right. (e.g., If it's 7.9 × 10^3, then move the decimal three spaces to the right, and you'd get 7900.)
3.14159 × 10^7 = 31415900
9.897752 × 10^6 = 9897752
2.468 × 10^7 = 24680000
Out of all the numbers mentioned in the question, 71,224,900 is the only one that's greater than 3.14159 × 10^7 = 31415900.